Voice discrimination in four primates - Candiotti, Agnes; Zuberbühler, Klaus; Lemasson, Alban (My University, 2013)
One accepted function of vocalisations is to convey information about the signaller, such as its age-sex class, motivation, or relationship with the recipient. Yet, in natural habitats individuals not only interact with conspecifics but also with members of other species. This is well documented for African forest monkeys, which form semi-permanent mixed-species groups that can persist for decades. Although members of such groups interact with each other on a daily basis, both physically and vocally, it is currently unknown whether they can discriminate familiar and unfamiliar voices of heterospecific group members. We addressed this question with playbacks on monkey species known to form polyspecific associations in the wild: red-capped mangabeys, Campbell's monkeys and Guereza colobus monkeys. We tested subjects' discrimination abilities of contact calls of familiar and unfamiliar female De Brazza monkeys. When pooling all species, subjects looked more often towards the speaker when hearing contact calls of unfamiliar than familiar callers. When testing De Brazza monkeys with their own calls, we found the same effect with the longest gaze durations after hearing unfamiliar voices. This suggests that primates can discriminate, not only between familiar and unfamiliar voices of conspecifics, but also between familiar and unfamiliar voices of heterospecifics living within a close proximity. (C) 2013 Elsevier B.V. All rights reserved.